The intersection of cannabis use and oral health among 2SLGBTQI+ youth: a qualitative study protocol - Abbas Jessani; Fabio Arriola-Pacheco; Alexia Athanasakos; Karla Kenny; Mario Brondani; Herenia P. Lawrence (BMC Oral Health)
Abstract Background Two-Spirit, lesbian, gay, bisexual, transgender, queer or questioning, intersex, or other sexual orientations and gender identities (2SLGBTQI+) youth face multiple social and structural disparities and barriers that contribute to a sense of mistrust in the provision of healthcare services, including oral health. Cannabis use is also high among 2SLGBTQI+ individuals; however, unknowns exist regarding recreational use and its impact on oral health. Our research aims to explore the intersectionality of 2SLGBTQI+ youth, oral health, and cannabis consumption. Methods This qualitative study, guided by community-based participatory research and interpretative phenomenological approaches, will recruit consenting 2SLGBTQI+ youth, aged 19 and older, accessing services at Youth Opportunities Unlimited in London, Canada. Approximately 25 to 30 participants will be recruited to complete a one-on-one in-depth interview or focus group to collect information on their perception about the relationships between cannabis use and oral health. Discussion Recognizing the self-perceived pathways through which cannabis impacts oral health will prompt the development of theories, raise awareness, and support advocacy efforts for and by 2SLGBTQI+ youth, while also providing valuable insights for the community and healthcare providers at large.